The 2030 Agenda and the Goal of Gender Equality - Reich, Nele (Institut für Sozialarbeit und Sozialpädagogik e. V., Beobachtungsstelle für gesellschaftspolitische Entwicklungen in Europa, 2017)
The member states of the United Nations are responsible for implementing the 2030 Agenda and its Sustainable Development Goals, short SDGs. All member states are confronted with the task of formulating national measures to translate the SDGs into concrete action. SDG 5 addresses gender equality. The Observatory compares in its work the developments and national approaches for the implementation of this SDGs in Germany, Estonia and Sweden.
European Approaches in Comparison
Keywords: Gleichstellungspolitik; Nachhaltigkeit; 301 Soziologie, Anthropologie; Agenda 2030; SDG; United Nations